Membrane Modification with Polydopamine to Improve Performances A Mini Review - Muchtar, Syawaliah; Yusuf, Mukramah; Mulyati, Sri; Syamsuddin, Yanna; Fathanah, Umi; Takagi, Ryosuke (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2023)
This paper provides an overview of some studies and investigations regarding the utilization of polydopamine as an additive in membrane fabrication. Polydopamine is widely used due to its high hydrophilicity and adhesive properties. The addition of polydopamine in to the membrane system mostly attributed to the improvement of membrane performance in terms of permeation, antifouling, and antibiofouling.